2023
DOI: 10.1097/acm.0000000000005620
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Analysis in Undergraduate and Postgraduate Medical Education: A Scoping Review

Yvonne Steinert,
Kimberly Fontes,
Sara Mortaz-Hejri
et al.

Abstract: Purpose Social network analysis (SNA) is a theoretical framework and analytical approach used to study relationships among individuals and groups. While SNA has been employed by many disciplines to understand social structures and dynamics of interpersonal relationships, little is known about its use in medical education. Mapping and synthesizing the scope of SNA in undergraduate and postgraduate medical education can inform educational practice and research. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…We concluded that by leveraging the imprint of these actions in an LMS and using metrics of SNA, differences can be spotted in the communicational patterns that go beyond simple participation recording. This finding aligns with the research conducted by Steinert et al [52], which suggests that SNA can be instrumental in examining team dynamics and knowledge exchange among peers. Additionally, Xu et al [53] investigated the roles of both students and teachers in online discussion forums using SNA, concluding that such forums enhance courses by aiding students in grasping core materials and topics.…”
Section: Discussionsupporting
confidence: 91%
“…We concluded that by leveraging the imprint of these actions in an LMS and using metrics of SNA, differences can be spotted in the communicational patterns that go beyond simple participation recording. This finding aligns with the research conducted by Steinert et al [52], which suggests that SNA can be instrumental in examining team dynamics and knowledge exchange among peers. Additionally, Xu et al [53] investigated the roles of both students and teachers in online discussion forums using SNA, concluding that such forums enhance courses by aiding students in grasping core materials and topics.…”
Section: Discussionsupporting
confidence: 91%
“…While SNA has gained the spotlight in medical education [7][8][9] , its application in undergraduate and postgraduate education remains limited 7 , particularly within undergraduate research. This study represents the rst attempt to empirically explore the social dynamics of advice-seeking behaviors within the undergraduate research community.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into the social mechanisms driving success, we must quantify and assess these interactions. Social network analysis (SNA) emerges as a powerful tool for understanding the complex dynamics of mentorship 7 and how they in uence research outcomes. SNA allows us to visualize adviceseeking interaction and identify patterns of advice-seeking within a community 8 .…”
Section: Introductionmentioning
confidence: 99%